Uno sguardo al ruolo delle donne giudici nella magistratura afghana tra passato e presente (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The paper briefly discusses some aspects related to the current state of the judicial system in Afghanistan in light of the chaotic evacuations that occurred in the summer of 2021 and the consequent loss of competencies due to many judges leaving the country or their job. The second part includes an interview with judge Tayeba Parsa.
Keywords: Afghanistan; giudici; giustizia; sistema giudiziario; evacuazione